Case Study: A Practitioner Perspective on Implementation of Sustainability Initiatives at the University of California, Davis - Kirk, Camille (Journal of Sustainability Perspectives, 2023)
For over a century, the University of California (UC), Davis campus has been a living laboratory to innovate and implement scalable solutions to sustainability challenges. Four recent sustainability efforts reviewed in this case study include the first Fossil Fuel Free Pathway Plan in the UC, a Voluntary University Review of UC Davis’ contributions to the Sustainable Development Goals, the Big Shift project to lower the district heating carbon footprint, and the climate change-driven Living Landscape Adaptation Plan. Sustained engagement of all sectors of the campus community is critical to successful adoption of these initiatives. Key success drivers include: a) use of data-driven decision making; b) intensivecollaboration among many stakeholders, c) inclusion of faculty and students as active participants, and d) an emphasis on sharing best practices and findings